Growth of Cd1-xZnxTe thin films with high Zn content by close-spaced sublimation. (October 2016) - Wu, Yanglin; Xu, Haitao; Ji, Huanhuan; Huang, Jian; Zhang, Jijun; Fang, Zebo; Tang, Ke; Liang, Xiaoyan; Xu, Run; Wang, Linjun
Abstract: The Cd1-x Znx Te films with a high x value of about 0.42 were achieved by close-spaced sublimation (CSS) method using a pre-alloyed CdZnTe source on the basis of two critical growth factors. A relatively high growth temperature is one of two key factors to achieve high Zn content in CdZnTe films. The x value of Cd1-x Znx Te varies from 0.10 to 0.42 as the substrate temperature changes from 100 to 500 °C under the pressure of 10 Pa. Moreover, it can be inferred that the sticking coefficient ratio of Zn to Cd is about 2.5–4 times at 500 °C than that at 400 °C. The other factor, more importantly, is the growth pressure, which should be below 10 Pa, while a high pressure of above 1000 Pa generally adopted in the Cd1-x Znx Te films using the CSS method always leads to Cd1-x Znx Te films with a low x value. The sudden increase of Zn vapor pressure under a growth pressure lower than 10 Pa is responsible for a high Zn content in the Cd1-x Znx Te films. Highlights: The CdZnTe films with Zn content as high as 0.42 are achieved. A high sticking coefficient ratio of Zn to Cd is one of two key factors to obtain CdZnTe films with a high Zn content. A high Zn vapor pressure under low growth pressure is another key factor to obtain CdZnTe films with a high Zn content.